Role of histone modification in the occurrence and development of osteoporosis - Sun, Pan; Huang, Tingrui; Huang, Chen; Wang, Yongjun; Tang, Dezhi (Frontiers in Endocrinology, 2022)
Osteoporosis is a systemic degenerative bone disease characterized by low bone mass and damage to bone microarchitecture, which increases bone fragility and susceptibility to fracture. The risk of osteoporosis increases with age; with the aging of the global population, osteoporosis is becoming more prevalent, adding to the societal healthcare burden. Histone modifications such as methylation, acetylation, ubiquitination, and ADP-ribosylation are closely related to the occurrence and development of osteoporosis. This article reviews recent studies on the role of histone modifications in osteoporosis. The existing evidence indicates that therapeutic targeting of these modifications to promote osteogenic differentiation and bone formation may be an effective treatment for this disease.